BRIDGE Model: Transformasi Kearifan Lokal Madura melalui English for Young Learners dalam Pembentukan Karakter Anak Usia Dini - Astuti, Ria; Fadilah (Institut Agama Islam Negeri Madura, 2026)
The degradation of Tengka ethical values among the younger generation in Madura highlights the urgency of preserving culture from an early age. English language learning is often separated from local cultural values, which has the potential to weaken children's cultural identity. This study aims to analyze the process of transforming Tengka values (abhental syahadat, asokon pribadi, andhap asor) and find an effective transformation model through the English for Young Learners program for character building in early childhood at RA Sabilillah Sampang. The research used a qualitative case study approach for four weeks in August 2025 with subjects including one principal, four teachers, twenty students in group B, and ten parents. Data collection techniques included non-participant observation, in-depth interviews, and documentation studies analyzed using the interactive model of Miles, Huberman, and Saldaña. The results of the study produced the BRIDGE (Building Respectful Identity through Dynamic Global Education) Model, which consists of five components: building a foundation of values, reflecting values in language, integrating values and language, developing character, and fostering cultural identity. The data showed that 78% of children were able to use English expressions of politeness that reflected the value of andhap asor, 75% demonstrated self-control (asokon pribadi), and 70% expressed firmness of belief (abhental syahadat). The BRIDGE model offers a systematic framework for integrating local wisdom with foreign language learning in early childhood education.